MICRO-DETERMINATION OF ITOPRIDE HYDROCHLORIDE IN PHARMACEUTICAL FORMULATIONS AND URINE SAMPLES USING ICP-ATOMIC EMISSIO SPECTROMETRY - SABRY KHALIL, (International Journal of Pharma and Bio Sciences, 2013)
Ion-associate complexes of Itopride hydrochloride with zinc(II) thiocyanate, sodium cobaltinitrite and ammonium reineckate are precipitated. The solubility of the ion associates at the optimum pH and ionic strength values have been examined. Saturated solutions were prepared at different temperatures ( 25 – 60oC ) under the optimum precipitation conditions and the metal ion contents ( zinc, chromium and cobalt ) in the supernatant were determined. The solubility products were thus calculated at different temperatures and the thermodynamic parameters ΔH, ΔG and ΔS were calculated. A new accurate and precise method based on inductively coupled plasma atomic emission spectrometry for the micro-determination of Itopride hydrochloride (0.63-71.08 μg/ml) in pure solutions, pharmaceutical formulations and urine samples is given.